Health literacy practices in social virtual worlds and the influence on health behaviour. (December 2018) - McElhinney, Evelyn; Kidd, Lisa; Cheater, Francine M.
This study explored how health information accessed via a 3D social virtual world and the representation of 'self' through the use of an avatar impact physical world health behaviour. In-depth interviews were conducted in a sample of 25 people, across 10 countries, who accessed health information in a virtual world (VW): 12 females and 13 males. Interviews were audio-recorded via private in-world voice chat or via private instant message. Thematic analysis was used to analyse the data. The social skills and practices evidenced demonstrate how the collective knowledge and skills of communities in VWs can influence improvements in individual and community health literacy through a distributed model. The findings offer support for moving away from the idea of health literacy as a set of skills which reside within an individual to a sociocultural model of health literacy. Social VWs can offer a place where people can access health information in multiple formats through the use of an avatar, which can influence changes in behaviour in the physical world and the VW. This can lead to an improvement in social skills and health literacy practices and represents a social model of health literacy.